Role Of The Unrealisable - Emmet, Dorothy. author. aut Link
X, 134 p.
Keywords: There are certain ideals that can never be realised yet play an important role in our thinking, our morality, and our politics: they include the final comprehensive Truth, the General Will, the absolute Good, and certain religious ideals. Our attempts to get closer to them profoundly influence what we do, and our concern for them informs our criticism of what we reject. In politics, in particular, too many idealists are under the illusion that these ideals can be realised and if disillusioned about this they too easily turn to cynicism - which is equally mistaken. This book looks at the role of such ideals in our intellectual and moral lives and in our politics by taking Kant's concept of the Regulative Ideal, and in so doing develops the concept itself further. Other thinkers whose ideas are considered in relation to this range from Plato to Iris Murdoch.